ANALISIS KEDINAMISAN KELOMPOK PETERNAK DI KECAMATAN TAEBENU KABUPATEN KUPANG NUSA TENGGARA TIMUR - Multivira B. Manoe; Maximilian M. J. Kapa; Alfetri N. P. Lango (Buletin Ilmiah Impas, 2022)
This research has been conducted at one livestock farmer groups in Oeletsala Village, Taebenu Sub District, Kupang Regency from June till July 2020. The aims of this research were to know; (1) the characteristics of the Beef Cattle farmers group at Nijbaki Oeletsala village; (2) the dynamism of farmer group in the village; (3) the obstacles’ faced by the members of the members of group in terms of their cattle development effort. The method used in this research was census method due to the number of population that was group member who were only consists of 25 people so all of them were taken as respondents. The determination of research location was taken purposively (purposive sampling). The result of research showed that; (1) the characteristics of the Beef Cattle farmers group at Nijbaki Oeletsala village, the age from each group member ranged from 40- 55 years. The last formal education that was were dominantly received by farmer was Senior High School stage. And the range of work experience by each member of farmer group was about 20 years old; (2) the dynamism rate of Nijbaki livestock farmer on Oetsala Village, is in the dynamic category with the rate score achievement of 3,98 with maximum percentage of 79,67%; (3)The obstacles’ faced by cattle farmer as group member was dealt with, the irrelevancies of group purpose that was formulated that the purpose made showing the lack of benefit that feet by all goup members, the obstacles from the group solidarity were, lack of meeting frequency time among all members of group, the next obstacles was dealt with the task group function that was the lack of selft awareness of each group members in finishing the determine task, and the last was the obstacle dealt with the group effectiveness in which the program on the work plan was not executed according to work the will of group member because the tasks given haven’t been done perfectly.